Globalization and Black Identity: Interrogating Local & Translocal Imagination in the New Transatlantic African Writings Kehinde and Americanah - Gilani, Syed Sumaira (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Geography plays a significant role in shaping the identity of an individual, especially, African ‘black’ identity. In the globalized era, black identity does not imply a stable signifier of the African race but is substantially contingent. The global interconnectedness has rendered the communication between different community’s complex and challenging. The diasporic encounters of Emecheta and Adichie draw a separate yet linked legacies of their local/translocal black experiences from which they elicit their understanding of the two global realms, Global North and Global South. The research article critically analyzes the major concerns of race and black identity in the select novels, Kehinde and Americanah. The argument tries to bring to the forefront two conflicting cultural and political forces, African and American/European, simultaneously transcending and celebrating the local and the translocal. As a consequence, the subjective identities of the character’s act as variables that perceive the racial difference on the one hand, and on the other, the difference helps contribute in their identity formation in hybrid spaces like America and Britain.